OPTIMALISASI WAKTU FERMENTASI UNTUK MENINGKATKAN KANDUNGAN BIOAKTIF TEPUNG LENGKUAS MERAH (Alpinia officinarum) MENGGUNAKAN Lactobacillus plantarum - Gembul, Delsiana; Fitasari, Eka; Rinanti, Rosyida Fajri; Kurniawan, Taufik (Universitas Tribhuwana Tunggadewi, 2025)
Red galangal (Alpinia officinarum) is an Indonesian native herb rich in bioactive compounds. Fermentation is a promising method to enhance these components. This study aimed to determine the optimal fermentation time using Lactobacillus plantarum to maximize the bioactive content of red galangal flour. A Randomized Block Design was employed, with fermentation times ranging from 1 to 7 days. The fermented flour was extracted using a two-step aqueous maceration process. Total phenolic content (TPC) and total flavonoid content (TFC) were analyzed spectrophotometrically. The results showed that fermentation significantly increased both TPC and TFC compared to the unfermented control. The optimal fermentation duration was 5 days, yielding the highest TPC of 1100.74 mg GAE/100 g and a significantly higher TFC of 34.30 mg QE/100 g (P 0.01). After this point, the bioactive content began to decline. This study demonstrates that a 5-day fermentation period is optimal for enhancing the phenolic and flavonoid compounds in red galangal flour, highlighting a viable method for developing functional food ingredients.